Time and Magnitude of Peak Concentration of Reactive Groundwater Contaminants Discharged to a River. Issue 1 (24th October 2016) - Taylor, Stewart W.; Guha, Hillol
Abstract: An analytical solution for calculating the contaminant discharge rate in an aquifer following an instantaneous release of reactive contaminant mass to groundwater is used to derive relationships for the time and magnitude of peak concentration in a river receiving the transported material. Relationships are developed for the time of peak concentration relative to the time of travel for the contaminant, and the magnitude of peak concentration relative to the concentration calculated at the time of travel. Both quantities are found to be a function of two dimensionless parameters characterizing advective‐dispersive‐reactive transport—the Peclet number and the Damkohler number. It is shown that the time to peak concentration may occur before the time of travel, considering advection and retardation only, depending on the magnitudes of the Peclet and Damkohler numbers. Similarly, the magnitude of peak concentration may exceed the concentration calculated assuming that the time of peak concentration coincides with time of travel for the contaminant. For large Damkohler numbers, equating the time of peak concentration with the time of travel for the contaminant can significantly underestimate peak concentrations. Abstract : Article Impact Statement: Time and magnitude of peak concentration of reactive contaminants in groundwater uniquely characterized by Damkohler and Peclet numbers.